ANALISIS PENGARUH PARIWISATA TERHADAP PRODUK DOMESTIK REGIONAL BRUTO KABUPATEN / KOTA PROVINSI JAWA TIMUR 2011-2014 - Yhoga Bagus Adhikrisna; Wahyu Hidayat; Zainal Arifin (Jurnal Ekonomi Pembangunan, 2016)
This research is a quantitative research using panel data, the data used in the form of time series (2011-2014) and (29 districts and 9 cities in East Java) cross section. The data used in this study are secondary data obtained from the Central Statistics Agency (BPS) and the Department of Culture and Tourism of the Province of East Java. The analytical method used is linear regression analysis with panel data models fixed effects Eviews 9 software tools are used. The results showed that the growth product regencies / regional gross domestic cities in East Java province from the year 2011-2014 increases by an average of 11,29 percent. F test results showed a variable number of tourists, the number of hotels and the number of simultaneous influential restaurants of the regional gross domestic product. T test results showed a variable number of tourists, the number of hotels and the number of restaurants individually significant effect with the positive direction of regional gross domestic product in the District / City in the province of East Java. Models using the fixed effects model produces R2 value of 98%.